2007
DOI: 10.1124/jpet.106.115204
|View full text |Cite
|
Sign up to set email alerts
|

Roles of 5-Hydroxytryptamine (5-HT) Receptor Subtypes in the Inhibitory Effects of 5-HT on C-Fiber Responses of Spinal Wide Dynamic Range Neurons in Rats

Abstract: 5-Hydroxytryptamine (5-HT; serotonin) plays an important role in the descending control of nociception. 5-HT and its receptors have been extensively studied in the modulation of nociceptive transmission at the spinal level using behavioral tests that may be affected by the effects of 5-HT on motor performance and skin temperature. Using electrophysiological methods, the present study aimed to systematically investigate the roles of 5-HT receptor subtypes on the inhibitory effects of 5-HT on responses of the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 32 publications
1
35
0
1
Order By: Relevance
“…Histological analysis showed the accuracy of microdialysis probe placements, the reaction of host tissue, and 5-HT fibers surrounding the probe Transverse sections of spinal cord at the level of the dialysing part of microdialysis probes (1mm) confirmed that probes were successfully inserted in the L4 segment of the dorsal horn (layers II, III, IV, V of Rexed [10,11]), ( Fig.1;Fig. 2-A).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Histological analysis showed the accuracy of microdialysis probe placements, the reaction of host tissue, and 5-HT fibers surrounding the probe Transverse sections of spinal cord at the level of the dialysing part of microdialysis probes (1mm) confirmed that probes were successfully inserted in the L4 segment of the dorsal horn (layers II, III, IV, V of Rexed [10,11]), ( Fig.1;Fig. 2-A).…”
Section: Resultsmentioning
confidence: 96%
“…Animals were placed in a spinal stereotactic aparatus (David Kopf Instruments, USA). A microdialysis probe (membrane diameter of 240μm, cut off of 6000 Daltons, CMA11/1 mm, CMA/Microdialysis, Sweden) was stereotactically inserted into the L4 dorsal horn segment of the spinal cord (vertebral body T13) [6] in layers II, III, IV, V of Rexed [10,11]. As proprioceptive areas are located within laminae III, IV, V the specific placement of the membrane of the probe allowed for sampling from proprioceptive areas within the dorsal horn.…”
Section: Stereotactic Microdialysis Probe Placement Into the Dorsal Hmentioning
confidence: 99%
“…1; supplemental Videos 1, 2, available at www.jneurosci.org as supplemental material). This stimulus intensity is approximately three times C-fiber threshold, which has been shown to approximate 1 mA in rats in vivo (Rygh et al, 2000;Liu et al, 2007), thus exciting the majority of A␦-and C-fibers. The pattern of activity that we observed is similar to AFI responses elsewhere in the nervous system (Murakami et al, 2004;Reinert et al, 2004;Gao et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Electrical stimulus intensities ranging from one to more than three times C-fiber threshold were applied in our study (Rygh et al, 2000;Liu et al, 2007). Additionally, we used innocuous palpation causing mainly A␤-fiber stimulation in naive animals.…”
Section: Discussionmentioning
confidence: 99%
“…Only rats with significant mechanical allodynia, whose 50% PWT in ipsilateral hind limb was lower than 4.0 g, were selected for further electrophysiological studies. min), end-expiratory CO 2 (3.5%-4.5%), and rectal temperature (36.5-37.5 °C), and maintained within these ranges [20,21] . During electrode advancement, electrical pulses (0.5 Hz, 0.3-ms pulse width, 0.4 mA) were applied to the ipsilateral sciatic nerve as search stimuli so that a neuron with no spontaneous firing could be identified.…”
Section: Assessment Of Mechanical Allodynia Mechanicalmentioning
confidence: 90%